Plant communities with yellow oat grass (Trisetum flavescens (L.) Pb.) in the submontane and montane regions of Slovenia - Petras Sackl, Tina (Hacquetia, 2012)
In the present study, we investigated plant communities with Yellow Oat Grass (Trisetum flavescens (L.) Pb.) in the submontane and montane regions of Slovenia. In 2005-2007 ninety-one relevés were collected by using the standard procedure of the Braun-Blanquet approach. Relevés were analysed with multivariate analysis and classified within two associations: Astrantio-Trisetetum (Polygono-Trisetion) and the Pastinaco-Arrhenatheretum (Arrhenatherion). Management practices, soil conditions and altitude were found to be significant factors for a further subdivision of both associations. Within the Astrantio-Trisetetum association three subassociations could be distinguished: -typicum, -buphthalmetosum and -trollietosum, and subassociations -typicum, -medicagetosum lupulinae, as well as -lolietosum subass. nova in the Pastinaco-Arrhenatheretum. The floristic composition and ecological characteristics of these plant communities are described and their implications for grassland conservation in Slovenia are discussed.
Keywords: anthropogenous grasslands; antropogena travišča; Astrantio-Trisetetum; Pastinaco-Arrhenatheretum; Slovenia; Slovenija; vegetacija; vegetation